Chemically modified liposomes carrying TRAIL target activated hepatic stellate cells and ameliorate hepatic fibrosis in vitro and in vivo - Li, Qinghua; Ding, Youcheng; Guo, Xinlai; Luo, Shenggen; Zhuang, Huiren; Zhou, JingE; Xu, Nan; Yan, Zhiqiang (Journal of cellular and molecular medicine, 2019)
At present, no satisfactory anti‐liver fibrosis drugs have been used clinically due to the poor targeting ability and short half‐life period. This study aimed to explore the effects of a new TRAIL (TNF‐related apoptosis‐inducing ligand) preparation that can target aHSCs (activated hepatic stellate cells) on liver fibrosis and explain the possible underlying mechanism. Using our self‐made drug carrier pPB‐SSL that specifically targets aHSCs, recombinant human TRAIL (rhTRAIL) protein was embedded in (named as pPB‐SSL‐TRAIL) and applied to treat liver fibrotic mice as well as 3T3 fibroblast cells and aHSCs. Through in vitro and in vivo experiments, we found that, compared with the groups treated with TRAIL (free rhTRAIL) and SSL‐TRAIL (rhTRAIL capsulated within unmodified liposome), the group treated with pPB‐SSL‐TRAIL nanoparticles showed significantly lower cell viability and higher cell apoptosis in vitro. The targeting delivering system pPB‐SSL also significantly enhanced the anti‐fibrotic effect, apoptosis induction and long circulation of rhTRAIL. After the treatment with pPB‐SSL‐TRAIL, apoptosis of aHSCs was notably increased and hepatic fibrosis in mice was remarkably alleviated. In vitro, pPB‐SSL‐TRAIL nanoparticles were mainly transported and located on membrane or into cytoplasm, but the particles were distributed mainly in mouse fibrotic liver and most on the cell membrane of aHSCs. In conclusion, rhTRAIL carried by pPB‐SSL delivering system has prolonged circulation in blood, be able to target aHSCs specifically, and alleviate fibrosis both in vitro and in vivo. It presents promising prospect in the therapy of liver fibrosis, and it is worthwhile for us to develop it for clinical use.